Mindfulness and schema therapy : a practical guide - Vreeswijk, Michiel van. (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2014)
Schema therapy is now firmly established as an effective treatment for borderline personality disorder, and new applications are constantly being explores. Among the most promising is schema mindfulness, an approach that integrates schema therapy with techniques of Mindfulness-Based Cognitive Therapy (MBCT). Mindfulness and Schema therapy presents an innovative protocol for schema mindfulness with eight sessions and two follow-up sessions. Structured in three section-theoretical background, therapist's guide and participant workbook-Mindfulness and Schema therapy explores how mindfulness can be used to better understand schema-triggered responses and how patients can learn to respond in more healthy ways toward themselves and others. Innovatively combining theory, research, and practical guidance, Mindfulness and Schema Therapy represents an invaluable resource for therapists and patients seeking the very latest developments in schema therapy. --Book Jacket.
About the authors -- Foreword -- Acknowledgments -- Theoretical background -- Introduction -- Schema therapy -- Mindfulness -- Training manual -- Framework -- Contraindications -- Training -- Pitfalls -- Conclusion -- Appendix: -- Part iii" participant workbook -- Participant workbook -- Appendix: homework sheets.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Attention; Schema-focused cognitive therapy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Attention; Schema-focused cognitive therapy; Electronic books; Electronic books